Thermal noise and the incessant vibration of the outer hair cells in the cochlea - W. Fritze; M. Steurer (Discrete Dynamics in Nature and Society)
The continual exposure of outer hair cells (OHCs) to thermal noise causes vibrations in resonant frequency. As these vibrations are backprojected, they should be recordable as audiofrequencies in the outer ear canal. But even though they are likely to be amplified in some areas by clustering in terms of the chaos theory, they cannot be picked up in the outer ear canal by currently available recording technologies. Conditions change in the presence of pathology, e.g. loss of OHCs and fibrous replacement: Clusters grow in size and amplitudes become larger so that the vibrations can be picked up as spontaneous oto-acoustic emissions (SOAEs) in the outer ear canal. Efforts are needed to demonstrate the presence of physiological OHC vibrations (emission by incessant vibration, EIV) by processing auditory recordings with statistical methods.